Accountability of the "Title" Hajj in Bugis Culture: Social Interaction and Self Control - Jurana Nurdin; Muhammad Ikbal Abdullah; Nina Yusnita Yamin; Rahayu Indriasari; Masruddin Karim; Muhammad Din; Ni Made Suwitri Parwati; Nurlaela Mapparessa (International Journal of Religious and Cultural Studies, 2022)
This study aims to find the meaning of accountability for Hajj’s “title” or designation from the perspective of Bugis culture. This study uses an interpretive paradigm with a symbolic interactionism approach. The informants in this study were Bugis people who have fulfilled the pilgrimage which were chosen in purposive manner. The data were analyzed by using the action patterns of the informants, which were obtained through real-life observations, as well as from interviews to understand the responses and interpretations of the informants. The study finds that the “title” of Hajj was interpreted as an action based on social value as well as self-control in behaving in society.